ECOSYSTEM SERVICES IN THE MID-HILL FOREST OF WESTERN NEPAL: A CASE OF PANCHASE PROTECTED FOREST - Bhandari, Ananta Ram; Khadka, Udhab Raj; Kanel, Keshav Raj (Journal of Institute of Science and Technology, 2018)
This paper identified ecosystem services of Panchase Protected Forest (PPF) in the mid-hills of western Nepal using the Economics of Ecosystem and Biodiversity (TEEB) framework. Transect walk, focus group discussion, key informants interview and expert’s consultation were used. This study revealed that PPF offered wide range of ecosystem services including provisioning, regulating habitat, and cultural and amenity services. Provisioning services offered by PPF included food (35 species), raw materials (22 species), energy (17 species), medicines (40 species), ornamental resources (3 species) and water resources. The forest was also a source of water for irrigation and domestic consumption. The regulating services offered by PPF included water flow regulation, erosion prevention, water purification, soil fertility maintenance, air quality regulation and climate regulation. PPF provided habitat for 589 species of flowering plants, 24 species of mammals and 262 species of birds maintaining life cycles and genetic diversity. By maintaining landscape integrity and heritages, PPF provided opportunities for recreation and tourism. A total of 3,600 tourists and 25,340 pilgrims visit PPF every year. The beneficiary of ecosystem services from PPF ranged from local level to sub-national, national and global levels.